2011
DOI: 10.3166/ga.24.49-60
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-Miocene exhumation of the Beni-Bousera peridotite through a lithosphere-scale extensional shear zone

Abstract: New structural data and P-T estimates of syn-deformational assemblages within the Beni Bousera peridotites and their crustal envelope are used to explain their Alpine exhumation. The Beni Bousera peridotites occur as thin sheets within high grade crustal units of the lower Sebtides (inner Rif, Morocco) and are composed of weakly deformed spinel lherzolite in the core of the massif and garnet-spinel mylonite at the rim. The main foliation trajectories in both the peridotites and overlying crustal units show sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…In addition to the occurrence of graphite pseudomorphs after diamond, thermobarometry data are consistent with very-high to high pressure and temperature conditions (Afiri et al, 2011;Gysi et al, 2011;Kornprobst et al, 1990;Pearson et al, 1995). For example, Kornprobst et al (1990) demonstrated that the Cpx-Gt associations in corundum-bearing garnet clinopyroxenites indicate temperatures as high as 1200-1350°C at 2 GPa.…”
Section: Introductionsupporting
confidence: 61%
“…In addition to the occurrence of graphite pseudomorphs after diamond, thermobarometry data are consistent with very-high to high pressure and temperature conditions (Afiri et al, 2011;Gysi et al, 2011;Kornprobst et al, 1990;Pearson et al, 1995). For example, Kornprobst et al (1990) demonstrated that the Cpx-Gt associations in corundum-bearing garnet clinopyroxenites indicate temperatures as high as 1200-1350°C at 2 GPa.…”
Section: Introductionsupporting
confidence: 61%
“…Such zircon ages, although somewhat younger (see Esteban et al, 2011a), were also reported from an orthogneiss of the Alpujarride complex [Zeck and Whitehouse, 1999: 285 ± 5 (2σ) Ma]. In spite of these Hercynian ages, at least the exhumation of the Ronda peridotite, as part of the subcontinental lithospheric mantle (Hidas et al, 2013, and references therein; refers also to the Beni Bousera peridotite massif), seems to be unequivocally an Early Miocene event, which was very fast (for the Beni Bousera peridotite massif: Afiri et al, 2011) and accompanied by a drastic thinning of the orogenic crust (Platt et al, 2003;Zeck, 1996). This could also explain the extensional tectonics in the Jubrique unit and the condensed crustal section as reported, for instance, by Balanyá et al (1993).…”
Section: Geological Settingmentioning
confidence: 88%
“…Both arcs have closeto-180 • curvatures with similar radii, can be explained in terms of slab rollback, show evidence for continental subduction (Morales et al, 1999), and have peridotites exposed along part of their length. The Beni Bousera peridotite (Rif Mountains, Morocco) is particularly analogous to Seram owing to its association with mylonitised kinzigites (aluminous garnet-sillimanite granulites) which have also been interpreted to form the hanging wall above sheared peridotites exhumed beneath a low-angle detachment (Afiri et al, 2011). Furthermore, the El Hoyazo region of the Betic Cordillera is one of very few other localities aside from Ambon where ambonites have been erupted, which similarly contain xenoliths of their granulitic protolith (Zeck, 1970;Zeck and Williams, 2002;Acosta-Vigil et al, 2010;Álvarez-Valero and Waters, 2010).…”
Section: Discussionmentioning
confidence: 99%